2009
DOI: 10.1097/gim.0b013e3181bd38a9
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype analysis of TCF4 mutations causing Pitt-Hopkins syndrome shows increased seizure activity with missense mutations

Abstract: Purpose: Pitt-Hopkins syndrome is characterized by severe mental retardation, characteristic dysmorphic features, and susceptibility to childhood-onset seizures and intermittent episodes of hyperventilation. This syndrome is caused by haploinsufficiency of TCF4, which encodes a basic helix-loop-helix transcription factor. Missense, nonsense, splicesite mutations, and gene deletions have been found in individuals with Pitt-Hopkins syndrome. Previous reports have suggested that the PittHopkins syndrome phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 41 publications
7
101
0
4
Order By: Relevance
“…Behaviour will also be influenced by interactions within social and learning environments and by reactions from that environment to the individual's tempera- [6][7][8][9][10][11]13,14,[30][31][32][33][34][35] Published cases with proven TCF4 mutations [6][7][8][9][10][11]13,14,[30][31][32][33][34][35] Present study ment, external features, and neuropsychological deficits. Studying phenotypes of rare and ultra-rare genetic syndromes associated with severe intellectual disability has made it clear that, although individual outcomes may arise from genetic differences, the expression of genes affecting structure, development and function of the brain is also influenced by the interplay between genes, learning, and social context, and too much emphasis on biological determinants should be avoided.…”
Section: Discussionmentioning
confidence: 95%
“…Behaviour will also be influenced by interactions within social and learning environments and by reactions from that environment to the individual's tempera- [6][7][8][9][10][11]13,14,[30][31][32][33][34][35] Published cases with proven TCF4 mutations [6][7][8][9][10][11]13,14,[30][31][32][33][34][35] Present study ment, external features, and neuropsychological deficits. Studying phenotypes of rare and ultra-rare genetic syndromes associated with severe intellectual disability has made it clear that, although individual outcomes may arise from genetic differences, the expression of genes affecting structure, development and function of the brain is also influenced by the interplay between genes, learning, and social context, and too much emphasis on biological determinants should be avoided.…”
Section: Discussionmentioning
confidence: 95%
“…In their genome scan metaanalysis of linkage studies on schizophrenia, Lewis et al [13] found the 18q21.1-qter 'bin' ranked around fifteenth in the genome. The TCF4 gene is involved in normal brain development [14] and has been associated with the Pitt-Hopkins syndrome, a severe encephalopathy with autonomic dysfunctions like intermittent hyperventilation [15][16][17][18] . Recently, Kalscheuer et al [19] reported a de novo translocation disrupting exon 4 of TCF4 in a girl with mental retardation, thus suggesting that there are also milder phenotypic expressions of TCF4 variability compared to the Pitt-Hopkins syndrome.…”
Section: Novel Schizophrenia Risk Gene Tcf4 Influences Verbal Learninmentioning
confidence: 99%
“…In this study, an interaction of TCF4 and MATH1, a proneural protein, on different neural progenitor populations was investigated and disrupted pontine nucleus development was found in TCF4 knock out mice. Second, several studies showed that TCF4 haploinsufficiency contributes to severe neurodevelopmental disorders such as the Pitt-Hopkins syndrome [1,4,9,33,40]. This autosomal dominant encephalopathy is characterized by severe mental retardation, microcephaly, disrupted motor development, and hyperventilation, as described above [25].…”
Section: Tcf4 and Cognitive Endophenotypes Of Schizophreniamentioning
confidence: 97%
“…Pitt-Hopkins syndrome was described in 1978 as a syndrome of mental retardation, microcephaly, facial dysmorphisms, and intermittent hyperventilation [25]. Seizures also frequently occur in the syndrome [33]. In 2008, it was shown that a mutation of TCF4 may also cause mental retardation without the associated features of Pitt-Hopkins syndrome, i.e.…”
Section: Introductionmentioning
confidence: 99%